PELATIHAN BROKER MELALUI SIMULASI ROLEPLAY DAN PENERAPAN STRATEGI MARKETING MIX 4P UNTUK MENINGKATKAN KEBERHASILAN PROSPEK NASABAH PERUSAHAAN BERJANGKA - Aquila Permadani, Kezia; Cordelia Izaak, Wilma (Education and Talent Development Center of Indonesia, 2025)
This community service activity was motivated by the lack of product understanding and communication skills among internship students who act as brokers or financial consultants at PT. Valbury Asia Futures. The purpose of this activity is to enhance students' competencies in dealing with prospective clients through roleplay training and the application of the 4P Marketing Mix strategy. The implementation method involves roleplay simulation training and applying the 4P Marketing Mix strategy, carried out in stages including preparation, execution, and evaluation over the course of a 4-month internship at the Surabaya branch office of PT. Valbury Asia Futures. The results show a significant improvement in self-confidence, communication skills, and success in client prospecting. In fact, six internship students acting as financial consultants have successfully closed deals with clients. This activity provides direct benefits in the form of improved human resource quality and contributes to the company's marketing success